2020
DOI: 10.1002/cpt.1783
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Intensive Antituberculosis Treatment of Tuberculous Meningitis

Abstract: The most effective antituberculosis drug treatment regimen for tuberculous meningitis is uncertain. We conducted a randomized controlled trial comparing standard treatment with a regimen intensified by rifampin 15 mg/kg and levofloxacin for the first 60 days. The intensified regimen did not improve survival or any other outcome. We therefore conducted a nested pharmacokinetic/pharmacodynamic study in 237 trial participants to define exposure–response relationships that might explain the trial results and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 34 publications
4
37
1
Order By: Relevance
“…For ethambutol, the PK was best described by a two-compartment model with first-order absorption and elimination, and this is consistent with previously published models (24,49,51). The elimination clearance in this study was higher than that in adult TB patients (24,49,51).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…For ethambutol, the PK was best described by a two-compartment model with first-order absorption and elimination, and this is consistent with previously published models (24,49,51). The elimination clearance in this study was higher than that in adult TB patients (24,49,51).…”
Section: Discussionsupporting
confidence: 90%
“…The values for rifampin plasma AUC 0–24 , corresponding to 50% of maximal survival (50% effective concentration [EC 50 ]), reported in those two studies were 86.4 mg×h/liter ( 21 ) and 171 mg×h/liter ( 22 ). Another study demonstrated that isoniazid exposure in plasma and cerebrospinal fluid (CSF) was associated with the risk of death in adults with TBM, estimating the EC 50 to be 7.03 mg×h/liter in both plasma and CSF ( 23 ). To date, no association between outcome and pyrazinamide and ethambutol exposures has been established in patients with TBM.…”
Section: Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Rifampin 15mg/kg increased plasma and CSF exposures compared to 10mg/kg: day 14 plasma AUC 0–24 increased from 48.2h•mg/L (range 18.2–93.8) to 82.5h•mg/L (range 8.7–161.0) and CSF AUC 0–24 from 3.5h•mg/L (range 1.2–9.6) to 6.0h•mg/L (range 0.7–15.1). However, within the exposure range achieved, no relationship between rifampin exposure and survival was seen within the trial 41 . It is possible, as seen in the PTB model 34 and in TBM PK-PD model 38 , a rifampicin dose of greater than 15mg/kg is required to achieve exposures capable of reducing time to culture conversion and improving survival, which may explain the lack of exposure-response relationship seen in this trial.…”
Section: Introductionmentioning
confidence: 88%